Suspected new-born child murder and concealment of pregnancy in Scotland, c.1812-c.1930 - Siddons, Timothy Peter (The University of Edinburgh, 2014)
This thesis explores the discovery, investigation and prosecution of, as well as the men and women involved as suspects and witnesses in, cases of suspected new-born child murder and concealment of pregnancy in Scotland between 1812 and 1930. The study utilises pre-trial and other legal documents relating to these cases to outline both the continuities with other studies and aspects of the subject that are peculiar to Scotland during the period. An examination of the pre-trial documents not only reveals the various responses to suspicions of pregnancy and murder by the local community, it also shows that in a number of cases investigators harboured suspicions that members of the community were involved, either as an accessory to a crime, or withholding evidence. However, this information is largely ignored by prosecutors, and the vast majority of those tried were the victims’ mothers, an outcome that this thesis argues was a combination of a number of legal and medico-legal processes and procedures. This thesis also argues that the information provided by the pre-trial evidence can provide a more nuanced understanding of these ‘crimes’ – particularly at a local level – that is otherwise obscured by official statistics, that in turn can be used to challenge the prevailing historical consensus that has developed around certain aspects of the subject. The first chapter provides the legal and medico-legal contexts. Chapters Two and Three look at the discovery of, and responses to, the signs of pregnancy, recent delivery and of the bodies of new-born infants. Chapter Three argues that whilst communities were quick to observe the signs of pregnancy, they were less inclined to inform the authorities of their suspicions until after the signs of delivery, or a body, had been discovered. Chapter 4 looks at the profiles of suspects, and also at the geography of the ‘crimes’, and Chapter 5 looks at those men and women suspected of being an accessory to murder, and of helping to conceal a pregnancy or an infant’s death. This chapter reveals that the pretrial documents reveal that in a number of cases investigators suspected relatives, friends, the victims’ fathers, and in some cases even doctors and midwives, to be involved in various ways in cases of suspected new-born child murder. As such it provides a strong challenge to the historiographical consensus that new-born child murder was a sex-specific crime, carried out by the victim’s mother, acting alone. Chapters 6 and 7 explore the role of the police and medical witnesses respectively, both prior to a formal accusation, and during the official investigation. Chapter 7 also includes a detailed look at the medical reports pertaining to the examination of suspects and the post mortem examination of the victims. The final chapter looks at the witnesses and evidence presented at the trial, focusing in particular on the medico-legal issues that made it difficult for prosecutors to secure a successful murder conviction. The chapter argues that whilst these issues could be part of a wider culture of sympathy towards new-born child murder suspects, the evidence from the verdicts and sentencing can also demonstrate a hardening of judicial attitudes over the period.
Keywords: infanticide; child murder; concealment of pregnancy; Scotland